(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The muscular system constitutes the main apparatus for movement in the human body. The condition and healthy functioning of this system directly affect the overall health of the organism. Today, pressing issues related to the muscular system, including muscle diseases, inflammation, dystrophies, and other pathologies, are raising significant concerns not only clinically but also in scientific research. This article examines the pathologies of the muscular system, their diagnostics, treatment methods, and modern scientific approaches. It provides information on new treatment methods for muscle diseases, including muscle dystrophy, myopathy, myositis, and geriatric diseases, with particular focus on the importance of gene therapy and cell therapy.